PEMANFAATAN FITOHORMON UNTUK PRODUKSI BIBIT KENTANG (Solanum tuberosum L.) SEHAT MELALUI KULTUR JARINGAN - Inderiati, Sitti; Tresianti, Tresianti; Parando, Cindy L.; Wisdawati, Eka (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2024)
Tissue culture is the primary method of propagating potato plants for the development of superior, pathogen-free seeds. One of the most critical aspects influencing tissue culture performance is the presence of growth hormones in the planting media. This study investigated the use of phytohormones found in coconut water as an alternative for pricey synthetic growth hormones. The purpose of study is to determine the optimal coconut water concentration for increasing potato seed growth and production potato plantlet. Explants were cut from potato plantlets and planted aseptically in Murashige and Skoog media, with coconut water added at varying concentrations as treatment. The experiment was designed using a completely randomized design, and the experimental data were analysed using analysis of variance and additional honest significant difference tests. The results showed that the treatment had a significant effect on the parameters of sprouting speed and root length, but not on the parameters of number of shoots, shoot height, and number of leaves. The 150 mg/l coconut water treatment resulted in the fastest micro shoots and the greatest number of leaves. The 100 mg/l coconut water treatment resulted in the highest number of shoots, shoot height, and root length. Based on these findings, it was determined that a coconut water concentration of 100 ml/l was more successful in promoting the growth and producing of potato plantlets than synthetic hormones, and therefore, may be recommended for developing potato tissue culture.